Quantum groups and Lie theory - Pressley, Andrew (London Mathematical Society lecture note series, 2001)
This book comprises an overview of the material presented at the 1999 Durham Symposium on Quantum Groups and includes contributions from many of the world's leading figures in this area. It will be of interest to researchers and will also be useful as a reference text for graduate courses.